Efeito do óleo essencial da casca de laranja (Citrus sinensis L.) no tratamento da asma induzida por ovalbumina em camundongos - Calisto, Valdete Kaliane da Silva (2023)
Asthma is a chronic inflammatory disease of the airways characterized by recurrent episodes of wheezing, shortness of breath and incessant coughing. It is estimated to affect around 300 million people worldwide. Seeking to study the anti-inflammatory effect of orange peel (Citrus sinensis L.) as a possible medicine to improve asthmatic treatment and taking into account that essential oils have good acceptability in the market and retain key characteristics of their sources, this work aims to to evaluate the effect of orange peel essential oil (OECL) on allergen-triggered airway inflammation in experimental asthma in Swiss and BALB/c mice. The study was carried out in experimental models in these two species, through the chromatographic analysis of the bioactive compounds of the OECL, presence of neutrophils, eosinophils and macrophages in the lungs, presence of eosinophils in the bronchoalveolar lavage (LBA), profile of cytokines interleukin (IL)-5, 10, 17, -1β and tumor necrosis factor alpha (TNF-α) in the lungs. Through these it was possible to report that: the OECL is rich in the terpene D-Limonene, the analysis of the LBA of the two species of animals induced to asthma demonstrated that the treatment with the OECL in the two highest doses (30 and 90 mg/kg) reduced the number of inflammatory cells to values close to those found in animals in the control group (without allergic stimulus), the result of Eosinophil peroxidase (EPO) in the lung tissue of the group of animals sensitized and challenged with ovalbumin (OVA) was significantly higher when compared to the other groups , with the exception of groups of animals treated with OECL, which did not show any significant difference. Furthermore, treatment with OECL at doses of 10 mg/kg and 30 mg/kg was able to significantly reduce myeloperoxidase (MPO) activity when compared to the OVA group. In this study, it was also shown that the cytokines IL-10 and TNF-α behaved similarly in OECL and in dexamethasone and in the other cytokines studied (IL-5,17 and -1β) it was not found a correlation in OECL. Therefore, it can be concluded that OECL is able to reduce the inflammatory response related to the asthmatic process.